Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1161/atvbaha.119.312952
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Biliary and Intestinal Cholesterol Secretion Reveals That CETP (Cholesteryl Ester Transfer Protein) Alters Elimination Route in Mice

Abstract: Objective: Determine the impact of CETP (cholesteryl ester transfer protein) on the route of cholesterol elimination in mice. Approach and Results: We adapted our protocol for biliary cholesterol secretion with published methods for measuring transintestinal cholesterol elimination. Bile was diverted and biliary lipid secretion maintained by infusion of bile acid. The proximal small bowel was perfused with bile acid micelles. In high-fat, high-cholester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Bile acids, the major endproduct of cholesterol metabolism, are synthesized in the liver and secreted via bile into the intestine to aid the absorption of fat-soluble vitamins and dietary fat (Di Ciaula et al, 2017). Simultaneous measurements of biliary and intestinal cholesterol secretion in mice showed that plasma cholesteryl ester transfer protein (CETP) altered the route of cholesterol elimination from the body in mice fed a high fat, high cholesterol diet (Li et al, 2019). Overexpression of bile salt hydrolase by a Lactobacillus strain reduced cholesterol absorption and increased cholesterol catabolism in mice fed a high cholesterol diet (Wang et al, 2019c).…”
Section: Discussionmentioning
confidence: 99%
“…Bile acids, the major endproduct of cholesterol metabolism, are synthesized in the liver and secreted via bile into the intestine to aid the absorption of fat-soluble vitamins and dietary fat (Di Ciaula et al, 2017). Simultaneous measurements of biliary and intestinal cholesterol secretion in mice showed that plasma cholesteryl ester transfer protein (CETP) altered the route of cholesterol elimination from the body in mice fed a high fat, high cholesterol diet (Li et al, 2019). Overexpression of bile salt hydrolase by a Lactobacillus strain reduced cholesterol absorption and increased cholesterol catabolism in mice fed a high cholesterol diet (Wang et al, 2019c).…”
Section: Discussionmentioning
confidence: 99%
“…Obicetrapib is a CETP inhibitor, ezetimibe is a Niemann Pick C1-Like-1 inhibitor, and statins inhibit 3-hydroxy-3-methylglutaryl coenzyme A reductase. In addition to impairing the transfer of cholesteryl esters from HDL to ApoB-containing particles, CETP inhibition may also increase transintestinal cholesterol excretion, which would contribute to fecal sterol excretion, and upregulate scavenger receptor class B type 1 and hepatic LDL receptor expression [ 30 , 74 , 75 ]. Further, previous studies on CETP inhibitors have demonstrated that there is a substantially increased catabolic rate of LDL and ApoB, which is the primary metabolic basis for their low plasma levels.…”
Section: Proposed Mechanisms Of Cetp Inhibitors Alone and In Combinat...mentioning
confidence: 99%
“…These results indicate that the LDL receptor pathway may also be upregulated by CETP inhibition [ 76 78 ]. The combination of these actions will reduce circulating LDL-C concentrations [ 30 , 35 •, 74 , 75 ].
Fig.
…”
Section: Proposed Mechanisms Of Cetp Inhibitors Alone and In Combinat...mentioning
confidence: 99%
“…An identically treated second cohort (n=7-8 per sex) underwent surgical assessment of biliary and intestinal cholesterol secretion rates as previously described with minor modifications. [30] Mice were anesthetized using 2% isoflurane (Henry Schein, Product Number 050033) and placed on a temperature-controlled heating pad system (Protech International Inc., TC-1000 Temperature Controller) to maintain a body temperature of 37 °C. Mice were supplied with oxygen (Scott Gross, Item Number 421) and isoflurane using a nose cone.…”
Section: Surgical Assessment Of Biliary and Intestinal Cholesterol Secretionmentioning
confidence: 99%